RELATION BETWEEN FEEDING PRACTICES AND DISEASE INCIDENCE IN DAIRY ANIMALS OF PUNJAB - KRISHANDEV; VERMA, HK; KASRIJA, R; SINGH, J (The Indian Journal of Animal Reproduction, 2016)
Dairy farmers (30 from each of the six different agro-climatic zones of Punjab state) rearing >5 dairy animals each were randomly selected and interviewed. In different zones of Punjab, there was variation (p<0.05) in feeding of green fodder and dry fodder to dairy animals. The concentrate feeding of lactating buffalo and pregnant-dry buffalo was also different (p<0.05). The green fodder, mineral mixture and concentrate feeding had negative and dry fodder feeding had positive correlation (p<0.05) with common diseases like mastitis, anestrus, repeat breeding and retention of placenta. In brief, appropriate feeding practices should be followed at a dairy farm for reducing the incidence of common diseases.